IgE sensitisation in relation to flow-independent nitric oxide exchange parameters - Norbäck Dan; Holmkvist Thomas; Janson Christer; Malinovschi Andrei; Meriläinen Pekka; Högman Marieann (Respiratory Research, 2006)
Abstract Background A positive association between IgE sensitisation and exhaled NO levels has been found in several studies, but there are no reports on the compartment of the lung that is responsible for the increase in exhaled NO levels seen in IgE-sensitised subjects. Methods The present study comprised 288 adult subjects from the European Community Respiratory Health Survey II who were investigated in terms of lung function, IgE sensitisation (sum of specific IgE), smoking history and presence of rhinitis and asthma. Mean airway tissue concentration of NO (CawNO), airway transfer factor for NO (DawNO), mean alveolar concentration of NO (CalvNO) and fractional exhaled concentration of NO at a flow rate of 50 mL s-1 (FENO 0.05) were determined using the extended NO analysis. Results IgE-sensitised subjects had higher levels (geometric mean) of FENO 0.05 (24.9 vs. 17.3 ppb) (p < 0.001), DawNO (10.5 vs. 8 mL s-1) (p = 0.02) and CawNO (124 vs. 107 ppb) (p < 0.001) and positive correlations were found between the sum of specific IgE and FENO 0.05, CawNO and DawNO levels (p < 0.001 for all correlations). Sensitisation to cat allergen was the major determinant of exhaled NO when adjusting for type of sensitisation. Rhinitis and asthma were not associated with the increase in exhaled NO variables after adjusting for the degree of IgE sensitisation. Conclusion The presence of IgE sensitisation and the degree of allergic sensitisation were related to the increase in airway NO transfer factor and the increase in NO concentration in the airway wall. Sensitisation to cat allergen was related to the highest increases in exhaled NO parameters. Our data suggest that exhaled NO is more a specific marker of allergic inflammation than a marker of asthma or rhinitis.